Early life adversity and males: Biology, behavior, and implications for fathers' parenting. (April 2022) - Condon, Eileen M.; Dettmer, Amanda; Baker, Ellie; McFaul, Ciara; Stover, Carla Smith
Highlights: Early life adversity (ELA) may influence fathers' parenting, but empirical evidence is limited. Males exposed to ELA are at increased risk for poor emotion regulation, aggressive behaviors, and insecure attachment. Research is needed to understand effects of ELA on males' hormones during the transition to fatherhood. Our conceptual framework may direct future research and interventions for fathers with ELA history. Abstract: Fathers have an important and unique influence on child development, but influences on fathers' parenting have been vastly understudied in the scientific literature. In particular, very little empirical research exists on the effects of early life adversity (ELA; e.g. childhood maltreatment, parental separation) on later parenting among fathers. In this review, we draw from both the human and non-human animal literature to examine the effects of ELA, specifically among males, in the following areas: 1) neurobiology and neurocognitive functioning, 2) hormones and hormone receptors, 3) gene-environment interactions and epigenetics, and 4) behavior and development. Based on these findings, we present a conceptual model to describe the biological and behavioral pathways through which exposure to ELA may influence parenting among males, with a goal of guiding future research and intervention development in this area. Empirical studies are needed to improve understanding of the relationship between ELA and father's parenting, inform the development of paternal and biparental interventions, and prevent intergenerational transmission of ELA.